The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1055/s-0042-1760256
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Protease-Activated Receptor-1 (PAR-1) Inhibition on Endothelial-Related Biomarkers in Patients with Coronary Artery Disease

Abstract: Background Vorapaxar has been shown to reduce cardiovascular mortality in post-myocardial infarction (MI) patients. Pharmacodynamic biomarker research related to protease-activated receptor-1 (PAR-1) inhibition with vorapaxar in humans has short follow-up (FU) duration and is mainly focused on platelets rather than endothelial cells. Aim This article assesses systemic changes in endothelial-related biomarkers during vorapaxar treatment compared with placebo at 30 days' FU and beyond, in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Some studies have verified that thrombin can activate Gαq and Gα12 signaling by cleavage in Arg41 to activate PAR‐1 (Marinissen et al., 2003). Vorapaxar is an active antiplatelet molecule, so it is always used as an inhibitor of PAR‐1 (Nilsen et al., 2023). Our study transfected sh‐NC and sh‐PAR‐1 with SUDHL2 cells or processed SUDHL2 cells through added thrombin, Vorapaxar, and Na 2 S 2 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have verified that thrombin can activate Gαq and Gα12 signaling by cleavage in Arg41 to activate PAR‐1 (Marinissen et al., 2003). Vorapaxar is an active antiplatelet molecule, so it is always used as an inhibitor of PAR‐1 (Nilsen et al., 2023). Our study transfected sh‐NC and sh‐PAR‐1 with SUDHL2 cells or processed SUDHL2 cells through added thrombin, Vorapaxar, and Na 2 S 2 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Vorapaxar (SCH530348), a US Food and Drug Administration-approved PAR1 inhibitor used in clinical trials as an antiplatelet agent on top of dual antiplatelet therapy, has had limited clinical uptake likely due to side effects of bleeding as reflected by a very long antiplatelet pharmacodynamic half-life of >4 weeks. 42 A recent publication 43 suggests that post-myocardial infarction or NSTEMI patients (N=265) receiving daily vorapaxar for 1 month may have increases in activated endothelial cells compared with the placebo cohort as indicated by significantly increased systemic levels of von Willebrand factor and E selectin, specific markers of endothelial cell activation. By comparison, PZ-128 is a reversible PAR1 antagonist with 50% recovery of PAR1 activity on platelets by 24 hours and 75% recovery by 8 to 14 days with no significantly increased bleeding in nonhuman primates 44 or coronary artery disease/acute coronary syndrome patients taking concomitant P 2 Y12 inhibitor (clopidogrel, prasugrel, and ticagrelor) and aspirin.…”
Section: Discussionmentioning
confidence: 99%
“…A phase 4 trial recently demonstrated that addition of vorapaxar to mono-or dual-antiplatelet therapy had no effect on clot characteristics or coagulation in patients with a history of MI or PAD, though it may have anti-inflammatory effects [54]. A more recent study examined endothelial cell biomarkers in a follow-up to the TRACER trial [52] and reported increases in pro-inflammatory biomarkers such as angiopoietin-like 4 (ANGPTL4) in patients who received vorapaxar treatment, suggesting that vorapaxar causes endothelial dysfunction [55].…”
Section: Par Antagonistsmentioning
confidence: 99%